Determinants of tomato farmers efficiency in Mymensingh district of Bangladesh: Data Envelopment Analysis approach (Journal of the Bangladesh Agricultural University, 2018)
Tomato is one of the major vegetables in Bangladesh that experienced massive productivity growth after independence. Nevertheless, farmers are struggling to find out optimal input combination in their farm that causes inefficient input use. Therefore, this study estimated the factors affecting efficiency of tomato farmers in Mymensingh of Bangladesh. Input oriented Data Envelopment Analysis (DEA) was employed for measuring efficiency while Tobit regression model was used to estimate the factors affecting efficiency. A total of 60 tomato farmers were selected using random sampling technique. Mean technical efficiency for tomato farmers was 0.83 implies that tomato farmers can reduce their input use by 17%. Education, training and high yielding variety adoption had positive effect on efficiency while age of tomato farmer’s had negative effect on efficiency. Efficiency increased with the farmer’s education, training and variety adoption. Farmer’s adopting local high yielding variety was more efficient than that of exotic high yielding variety. In addition, efficiency of farmers reduced with their age. Improvement of tomato farmer’s efficiency is possible if farmers received education, training and local high yielding variety.J. Bangladesh Agril. Univ. 16(1): 93-97, April 2018